2012
DOI: 10.1016/j.colsurfb.2012.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic properties of prussian blue nanoparticles supported on poly(m-aminobenzenesulphonic acid)-functionalised single-walled carbon nanotubes towards the detection of dopamine

Abstract: Edged plane pyrolytic graphite electrode (EPPGE) was modified with and without Prussian blue (PB) nanoparticles and polyaminobenzene sulphonated single-walled carbon nanotubes (SWCNTPABS) using the chemical deposition method. The electrodes were characterised using microscopy, spectroscopy and electrochemical techniques. Results showed that edged plane pyrolytic graphite-single-walled carbon nanotubes-prussian blue (EPPGE-SWCNT-PB) electrode gave the best dopamine (DA) current response which increases with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 58 publications
6
31
4
Order By: Relevance
“…Figure (A) (using CoPc NP ‐GCE as an example) shows LSV plots obtained after keeping the electrode in a stirred solution for 20 min (to allow for adsorption). Applying the Langmuir adsorption theory (Equation ), a plot of the ratio of hydrogen peroxide concentration to catalytic current against concentration of hydrogen peroxide was linear, which is indicative of adsorption further consolidating the observed high Tafel slopes. true[H2O2]Icat=1βImax+[H2O2]Itrueprefixmax …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Figure (A) (using CoPc NP ‐GCE as an example) shows LSV plots obtained after keeping the electrode in a stirred solution for 20 min (to allow for adsorption). Applying the Langmuir adsorption theory (Equation ), a plot of the ratio of hydrogen peroxide concentration to catalytic current against concentration of hydrogen peroxide was linear, which is indicative of adsorption further consolidating the observed high Tafel slopes. true[H2O2]Icat=1βImax+[H2O2]Itrueprefixmax …”
Section: Resultssupporting
confidence: 80%
“…Using equation 6 which relates Gibbs free energy change due to adsorption (ΔG°) to the adsorption equilibrium constant β, ΔG° was found to be −17.71 k J mol −1 for CoPc NP‐ GCE. This value is comparable to those reported elsewhere for high Tafel slopes . Eqn.…”
Section: Resultsmentioning
confidence: 99%
“…PB, an electron transfer mediator, has been used in the fabrication of our sensor, which catalyses the reduction of hydrogen peroxide in nature [13]. PB is a polynuclear and mixed-valent iron cyanide complex with a repeating unit of potassium ferrous ferricyanide hexacyano hexahydrate (Fe 4 (III)[Fe(II)(CN) 6 ] 3 ) [14]. Moreover, previous studies have shown that PB markedly enhanced the performance of carbon composite materials of biosensors [15,16].…”
Section: Introductionmentioning
confidence: 98%
“…Dopamine is a well-known catecholamine and a neurotransmitter (Schultz 1997;Komathi, Gopalan, and Lee 2010;Adekunle et al 2012;Dong et al 2012;Pandey and Pandey 2013). Dopamine affects a variety of physiological processes (Adekunle et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine affects a variety of physiological processes (Adekunle et al 2012). The concentration of dopamine may be determined electrochemically.…”
Section: Introductionmentioning
confidence: 99%